2021
DOI: 10.24996/ijs.2021.62.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Organic Geochemistry and Thermal Maturity Assessment of Cretaceous Balambo Formation from Selected Sites, Kurdistan, NE Iraq

Abstract: The Cretaceous Balambo Formation from three sections in Kurdistan Region of Northern Iraq was studied. The selected sections are located in the Zagros Fold -Thrust Belt. Eleven rock samples were analyzed by means of the organic geochemical method, Bitumen extraction method, and gas chromatography/mass spectrometry to determine the bitumen and hydrocarbon content, kerogen types, origin of organic matter, thermal maturity level, and depositional environment. The analyzed samples are considered to have an excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…The Ratawi, Sulaiy, and Balambo formations are among sequences that might create excellent source rocks, but the bulk of the Cretaceous rock units found in Iraq's petroleum system are reservoirs, including the Qamchuqa, Dokan, Kometan, and Shiranish formations [4]. Some studies have evaluated the potential of source rocks and the capacity of Cretaceous sediments to produce petroleum, one research was carried out by Sarraj and Mohialdeen [5] which studied Balambo Formation in Sulaimani Governorate. According to the findings, the formation has type II kerogen (oil prone), and type II/III (oil/gas prone) kerogen and based on the GC-MS parameters the samples are mature, although Al-Habba and Abdullah [6] in their study entitled, a geochemical study of hydrocarbon source rocks in northwestern Iraq, indicated that the Balambo Formation can be considered excellent source rock.…”
Section: Introductionmentioning
confidence: 99%
“…The Ratawi, Sulaiy, and Balambo formations are among sequences that might create excellent source rocks, but the bulk of the Cretaceous rock units found in Iraq's petroleum system are reservoirs, including the Qamchuqa, Dokan, Kometan, and Shiranish formations [4]. Some studies have evaluated the potential of source rocks and the capacity of Cretaceous sediments to produce petroleum, one research was carried out by Sarraj and Mohialdeen [5] which studied Balambo Formation in Sulaimani Governorate. According to the findings, the formation has type II kerogen (oil prone), and type II/III (oil/gas prone) kerogen and based on the GC-MS parameters the samples are mature, although Al-Habba and Abdullah [6] in their study entitled, a geochemical study of hydrocarbon source rocks in northwestern Iraq, indicated that the Balambo Formation can be considered excellent source rock.…”
Section: Introductionmentioning
confidence: 99%